Pingu virus: A new picornavirus in penguins from Antarctica - de Souza, William Marciel; Fumagalli, Marcílio Jorge; Martin, Matheus Cavalheiro; de Araujo, Jansen; Orsi, Maria Angela; Sanfilippo, Luiz Francisco; Modha, Sejal; Durigon, Edison Luiz; Proença-Módena, José Luiz; Arns, Clarice Weis; Murcia, Pablo Ramiro; Figueiredo, Luiz Tadeu Moraes (Virus Evolution, 2019)
Abstract Picornaviridae family comprises single-stranded, positive-sense RNA viruses distributed into forty-seven genera. Picornaviruses have a broad host range and geographic distribution in all continents. In this study, we applied a high-throughput sequencing approach to examine the presence of picornaviruses in penguins from King George Island, Antarctica. We discovered and characterized a novel picornavirus from cloacal swab samples of gentoo penguins (Pygoscelis papua), which we tentatively named Pingu virus. Also, using RT-PCR we detected this virus in 12.9 per cent of cloacal swabs derived from P. papua, but not in samples from adélie penguins (Pygoscelis adeliae) or chinstrap penguins (Pygoscelis antarcticus). Attempts to isolate the virus in a chicken cell line and in embryonated chicken eggs were unsuccessful. Our results expand the viral diversity, host range, and geographical distribution of the Picornaviridae.